Enhancing Inclusive Access to Justice in Uzbekistan - Muhammadiyev Bahrоmjоn Qоdirjоn (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
Access to justice is a fundamental element in realizing an inclusive and democratic rule of law. In Uzbekistan, various reforms have been undertaken to enhance the affordability and accessibility of legal services for all members of society, particularly vulnerable groups such as women, children, and rural communities. However, several obstacles remain, including complex legal bureaucracy and a lack of public awareness regarding their legal rights. This study aims to analyze legal policies aimed at improving access to justice, identify the challenges faced, and explore strategies that have been implemented to create a more inclusive legal system. The research adopts a juridical approach, examining existing regulations and policies, along with an empirical analysis of the implementation of those policies in practice. The findings show that Uzbekistan has taken several progressive steps, including institutional reforms, the digitalization of the judicial system, and the provision of free legal aid. Nevertheless, challenges such as limited resources, rigid bureaucracy, and unequal access in rural areas remain major barriers. Therefore, a more integrated and collaborative approach involving the government, civil society organizations, and international institutions is required to ensure equitable justice for all citizens.